Day 3 - 1100 - Edmund Morris.pdf - Gill, Philip (Cranfield University, 2023)
Understanding the Structural Properties of Nitrocellulose Edmund Morris - University of Edinburgh 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'